Morphological redescription and molecular characterization of Trichodina matsu Basson & Van As, 1994 (Ciliophora, Mobilida, Trichodinidae) infecting Tachysurus fulvidraco (Richardson, 1846) from Chongqing, China - Zhou, Qian; Tang, Fahui; Zhao, Yuanjun (Zootaxa, 2021)
During a survey of parasitic ciliates in Chongqing, China, Trichodina matsu Basson & Van As, 1994 was isolated from gills of Tachysurus fulvidraco. Furthermore, the 18S rRNA gene and ITS-5.8S rRNA region of T. matsu were sequenced for the first time and applied for the species identification and comparison with similar species in the present study. Based on the morphological and molecular comparisons, the results indicate that T. matsu is an ectoparasite specific for the Siluriformes catfish. Based on the analyses of genetic distance, multiple sequence alignments, and phylogenetic analyses, no obvious differentiation within populations of T. matsu was found. In addition, the ‘Trichodina hyperparasitis’ (KX904933) in GenBank is a misidentification and appears to be conspecific with T. matsu according to the comparison of morphological and molecular data.